Plant growth-promoting properties of cultivable endophytic root nodule bacterial isolates from Acacia mangium Willd - Syafikah Ismail, Fatin; Malahubban, Masnindah; Hailmi Sajili, Mohammad; Fitri Ab. Aziz, Zakry (Research in Plant Biology, 2016)
The present study was conducted to isolate and characterize endophytic bacteria isolated from root nodules of Acacia mangium Willd and subsequently tested for plant growth promotion. A total of five bacterial isolates were successfully isolated and subjected to morphological and biochemical examination. The present study found that all isolates had almost similar morphologically but differed in growth rate. All isolates were negative on N-free and IAA tests, though positive on P solubilisation test. The present study demonstrated that the inoculation with isolate FSI3 had significantly improved (p<0.05) root and shoot dry weight of winged bean seedlings as compared to uninoculated control. However, the inoculation did not significantly alter (p>0.05) root and shoot length of winged bean seedlings. The present study suggests that the stimulatory effect by isolate FSI3 may be associated with P-solubilizing ability. A further test on isolate FSI3 is considered essential in future to uncover the several other possible plant growth-promoting mechanisms.Â